A footprint of rainfall on land seismic data repeatability at the CO2 storage pilot site, Ketzin, Germany - Kashubin, A.; Juhlin, Christopher; Malehmir, A.; LüTh, S.; Ivanova, A.; Juhojuntti, N. (2011)
Two vintages of land time-lapse seismic data were acquired in 2005 and in 2009 at the Ketzin CO2 storage site in Germany. The datasets showed some differences in frequency content, signal-to-noise ratio and refraction statics despite that they were acquired with the same equipment and during the same seasons. The spatial variations in the data appeared to show good correlation with the difference in precipitation during the campaigns. These observations provide a ground for estimation of spatially varying operators that may be used in pre-stack or post-stack cross-equalization corrections of the time-lapse datasets.